Upaya Meningkatkan Hasil Belajar Siswa menggunakan Model Problem Based Learning (PBL) Materi Indahnya Saling Menghargai dalam Keberagaman - Gusmi Hayati Zamzami (Academia Edu Cendekia Indonesia (AEDUCIA), 2024)
Learning outcomes are basically an ability in the form of new skills and behaviors as a result of training or experience gained. Learning results in a person are often not immediately apparent without a person taking action to show the ability he has gained through learning. The purpose of this study was to determine the improvement of learning outcomes on the beautiful material of mutual respect in student diversity through the Problem-Based Learning (PBL) model. The research method uses Classroom Action Research (PTK). This research was conducted in the 2023/2024 school year. The research sample was fourth-grade students totaling 16 students. Data collection using observation, tests, and documentation. The data analysis technique used in this research is the minimum completeness criteria. The results showed that learning using the Problem-Based Learning (PBL) model can improve the learning outcomes of fourth-grade students in the field of Islamic Religious Education (PAI), the beautiful material of respecting each other in the diversity of students at school.